Conceptual model for cloud computing acceptance in the audit profession : Konceptualni model prihvaćanja uslužnog računalstva u revizorskoj profesiji - Dobrinić, Dunja (Array, 2021)
The paper proposes a conceptual model of cloud computing acceptance. The model includes variables from TAM (Technology Acceptance Model), TOE (Technology-organization-environment) framework, and the security risk variable. This study aims to verify the suitability of the proposed model for measuring cloud computing acceptance by the auditors and auditors' assistants in the Republic of Croatia. For the purposes of the study, data were collected through a questionnaire. The sample included 111 certified auditors and 28 auditing assistants. The structural equation modeling (SEM) method was used to analyze the data collected and evaluate the proposed model. The results confirmed the impact of perceived usefulness and time and complexity on the intention to use. The influence of image, education, perceived ease of use and security risk on perceived usefulness was confirmed, while the effect of perceived ease of use on the intention to use did not prove significant. Constructs perceived usefulness, perceived ease of use, and time and complexity explain 31% of the variance in intention to use cloud computing. The paper outlines the limitations of the research as well as the scientific contribution.